Iowa Birdline update, November 23, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for November 23, 1992. The highlights for the update include sightings of a Black Scoter, a flock of Red Crossbills and an exotic pair of Ringed Turtle-Doves, Also included are handwritten notes with sightings of 25 Bald Eagles at Lock Number 19 at Keokuk and a Ross' Goose among the waterfowl at Bay Branch. Epson - sheet feed/flatbed